1997
DOI: 10.2337/diacare.20.1.77
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Prepubertal Diabetes Duration on Diabetes: Microvascular Complications in Early and Late Adolescence

Abstract: Prepubertal subjects with diabetes did not have less retinopathy or elevated albumin excretion compared with pubertal subjects of the same age. Prepubertal diabetes duration is significantly related to the presence of retinopathy in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
1
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 16 publications
3
70
1
2
Order By: Relevance
“…These results suggest that the presence of ICAs and IAAs at diagnosis does not influence the development of complications. Rather, known predictors of microvascular complications include longer diabetes duration, especially for the prepubertal years with diabetes and health care utilization (47)(48)(49). The association of higher GAD titer levels at diagnosis with pupillary abnormalities is consistent with the previous report of higher titers at the time of diagnosis of peripheral neuropathy (45).…”
Section: Tpoas and Development Of Thyroid Diseasesupporting
confidence: 81%
See 1 more Smart Citation
“…These results suggest that the presence of ICAs and IAAs at diagnosis does not influence the development of complications. Rather, known predictors of microvascular complications include longer diabetes duration, especially for the prepubertal years with diabetes and health care utilization (47)(48)(49). The association of higher GAD titer levels at diagnosis with pupillary abnormalities is consistent with the previous report of higher titers at the time of diagnosis of peripheral neuropathy (45).…”
Section: Tpoas and Development Of Thyroid Diseasesupporting
confidence: 81%
“…Celiac disease was confirmed by small-bowel biopsy and was offered to all patients with positive AGA or EMA titers. Screening for microvascular complications was undertaken 3.1-13.4 years after diagnosis at the Children's Hospital at Westmead and included assessments of retinopathy, nephropathy, and autonomic and peripheral neuropathy (47)(48)(49)(50). Retinopathy was defined as the presence of at least one microaneurysm or hemorrhage in at least one eye detected by seven-field stereoscopic fundal photography (48).…”
Section: Research Design and Methods -From A New Southmentioning
confidence: 99%
“…This finding is in contrast with some longitudinal studies in which the duration of prepubertal diabetes seemed to have limited effect on longterm complications (32). This study also demonstrated a high prevalence of microalbuminuria, which was higher in the older children, in accordance with other studies (33). There was no correlation between duration of diabetes and occurrence of microalbuminuria.…”
contrasting
confidence: 57%
“…Retinopathy has been reported to be present with diabetes duration of 1-2 years (171,172); however, it usually is not recognized before 5-10 years of diabetes duration (80,(172)(173)(174). Although retinopathy is most commonly described after the onset of puberty, retinopathy can occur in prepubertal children (175).…”
Section: Retinopathymentioning
confidence: 99%